2012
DOI: 10.1007/s00424-012-1124-9
|View full text |Cite
|
Sign up to set email alerts
|

Phospholamban phosphorylation increases the passive calcium leak from cardiac sarcoplasmic reticulum

Abstract: Phospholamban (PLN) is a 52 amino acid integral membrane protein of the sarcoplasmic reticulum (SR) that exists in both monomeric and pentameric forms. In its unphosphorylated state, PLN inhibits the SR Ca(2+) ATPase (SERCA). This inhibition is relieved when PLN is phosphorylated as a result of β-adrenergic stimulation of the heart. Consistent with some predictions from molecular models and from functional studies of PLN incorporated into planar lipid bilayers, it has also been postulated that pentameric PLN c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…In the present study, we examined changes in the levels of PLB Ser-16 phosphorylation with a focus on the beta-adrenergic pathway. It has been demonstrated that reduced PKA-dependent PLB phosphorylation during HF may be due to changes at various levels of the betaadrenergic signaling pathway [6,11,12]. Decreases in PLB levels and/or changes in phosphorylation can directly impact SR Ca 2+ -uptake and muscle contractility [30], which is consistent with our finding that the β-adrenergic response to isoproterenol was impaired in the HF group but not in the INF group.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, we examined changes in the levels of PLB Ser-16 phosphorylation with a focus on the beta-adrenergic pathway. It has been demonstrated that reduced PKA-dependent PLB phosphorylation during HF may be due to changes at various levels of the betaadrenergic signaling pathway [6,11,12]. Decreases in PLB levels and/or changes in phosphorylation can directly impact SR Ca 2+ -uptake and muscle contractility [30], which is consistent with our finding that the β-adrenergic response to isoproterenol was impaired in the HF group but not in the INF group.…”
Section: Discussionsupporting
confidence: 91%
“…Free energy calculations show that the energy barrier for Ca 2+ ion transport is ~40 kcal/mol, which is prohibitive in the absence of an energy source (Becucci et al , 2009). A recent paper opened up the possibility that phosphorylation at Ser16 might be responsible for ion transport or Ca 2+ leakage (Aschar-Sobbi et al , 2012), motivating our structural studies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the coupling between cytoplasmic and transmembrane regions has been shown to be critical in the overall regulation process of SERCA 45 . The observed enhancement in structural dynamics upon phosphorylation may be at the origin of the perturbation in the equilibrium between PLN monomers and pentamers, which is key to regulate the amount of free monomers available for SERCA binding and therefore the apparent affinity of SERCA for Ca 2+ in its physiological window 29 32 46 47 .…”
Section: Discussionmentioning
confidence: 99%